Overview of Nigeria’s Infrastructural Development - Audu, Muhammad Onoruiza; Adeiza, Otu Muhammed (CSID Journal of Infrastructure Development, 2024)
This paper offers a comprehensive analysis of Nigeria’s infrastructural development from 2014 to 2023, focusing on significant achievements and recurring challenges. The study examines key projects in transportation, energy, and housing, such as the Abuja-Kaduna and Lagos-Ibadan railways, the Azura-Edo Power Plant, and urban road upgrades. Persistent issues, including insufficient funding, regulatory inefficiencies, regional disparities, and security challenges, are also assessed. Using a mixed-methods approach that incorporates a literature review, data analysis, and stakeholder perspectives, the research evaluates the social and economic effects of these initiatives. The findings provide strategic recommendations to improve infrastructure quality and accessibility, promote sustainable practices, and support long-term economic development.